Impact of Public Goods on Economic Growth Gaps among Regions of China - from the Perspective of Public Finance - Maoguo Wu; Tanyue Sun; Yu Zhou (European Scientific Journal, ESJ, 2016)
Based on the economic growth model of public expenditures, this paper assesses the contribution of public expenditures to economic growth among the East, Centre and West of China from 2007 to 2014. This paper attempts to explain the differences of the output per capita in these three regions from the perspective of disparities of investment in public goods determined by public finance and finds that public expenditures have effects on regional differences so that proper types of fiscal expenditures should be invested based on the regional economic characteristics.